Does Due Professional Care, Time Budget Pressure, Accountability, and Audit Experience effect on Audit Quality? - Sari, Arista Fauzi Kartika; Fakhriyyah, Dewi Diah (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 19 No 1 (2024), 2024)
External auditors or public accountants have an important role in society regarding the reliability of a company's financial reports. Public accountants also provide opinions about the fairness of financial reports that can be used for decision making. Therefore, public accountants need to provide quality audit services. This research aims to test the effect due professional care, time budget pressure, accountability, and work experience on audit quality. The research population is auditors Public Accountant Firm in Malang who are registered with the OJK. The sampling technique used convenience sampling and the sample size was determined using the Slovin formula. The data analysis method uses multiple linear regression analysis. The research results show that due professional care, accountability, and work experience have a significant positive effect on audit quality. While time budget pressure has no effect on audit quality. The implication of this research is that for public accounting firms to be able to produce high quality audits, they need to ensure the implementation of due professional care, accountability, and increase the auditor's work experience. Keywords : due professional care, time budget pressure, audit quality, accountability